Effects of workplace friendship on employee engagement. - Teo, Kenji. (2008)
There have been studies on employee engagement and workplace friendship separately. However there is almost no research on the effects of workplace friendship on employee engagement. This study examines the effect of workplace friendship on employee engagement. A survey was completed by 50 employees from various organizations and positions. The findings of this study has shown that perceived organizational support is a strong predictor of job and organization engagement, perceived supervisor support is not a predictor for job and organization engagement. Also found in this study, employee engagement is a predictor of organizational commitment, employee engagement mediates partially the relationship between its antecedents and consequences and finally, workplace friendship is a predictor of organization engagement but not job engagement. Limitations, implications and future research to be directed are also discussed.